Genipin Crosslinked Blended Collagen-Chondroitin: A Promising Biomaterial Scaffold Candidate for Cartilage Reconstruction - Trimartani Trimartani; Normalina Sandora; Bambang Hermani; Jeanne A Pawitan; Raden Ayu Anatriera (HAYATI Journal of Biosciences, 2022)
Tissue engineering offers a solution to the shortage of materials for cartilage reconstruction surgery by providing various potential biomaterial scaffolds. Tissue engineering utilizes biological or synthetic biomaterials as a scaffold for the host cells to repopulate and regenerate the tissue. The natural biomaterials such collagen and chondroitin imitates native cartilage matrix composition. Genipin as one of natural crosslinkers was added to improve the matrix biomechanical properties. This study was done to investigate biocomposition of blended collagen type 1, collagen type 2, chondroitin sulphate (Col1-Col2-CS) and genipin for its cytotoxicity using human umbilical mesenchymal stem cells (hUCMSCs), surface morphology, and biochemical composition. Genipin-crosslinked collagen-chondroitin biocomposite showed a homogeneous shape while uncrosslinked biocomposite had rough surface and fibrillar folds size. Spectroscopy demonstrated both biocomposites had similar peak resemble to no alternation of the biocomposition by crosslinking. Both types of biocomposites were biocompatible and had no toxic effects, as compared to the cell colony only (p value = 0.26). The conclusion are blended composite of collagen chondroitin crosslinked with genipin had generated a fine microstructure scaffold with smaller pore size, had similar biomolecular component spectrum absorption, and no exhibition of residual toxicity.